Pengaruh Kepercayaan Merek dan Kepuasan Pelanggan Pada Loyalitas Pelanggan Produk Antimo di Yogyakarta - , GANDES SITORESMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to examine the effect of brand trust and customer satisfaction of Antimo product in Yogyakarta on customer loyalty of Antimo product in Yogyakarta. This study conducted a quantitative approach with survey method, using primary data from consumers. The population in this study were all consumer of Antimo product in Yogyakarta. The sample in this study were some consumers of Antimo product in Yogyakarta. The sampling used purposive sampling/judgment sampling, which obtained 230 respondents who use the product in Yogyakarta and eligible for the study's respondents. The data analysis methods employed in this study was multiple regression analysis and the hypothesis testing used t-test. Based on the results of the regression test conducted, the study reveals that the two variables which are brand trust and customer satisfaction have a positive effect on customer loyalty of Antimo product in Yogyakarta.